2013
DOI: 10.3846/16111699.2011.631743
|View full text |Cite
|
Sign up to set email alerts
|

Testing Rational Expectations Hypothesis in the Manufacturing Sector in Malaysia

Abstract: The application of rational expectations hypothesis (REH) in macroeconomic research has marked a revolution in economic thinking, and the magnitude of its impact on the world of economics is undeniably significant. However, the extent to which REH applies in real-world settings is ambiguous even though the concept of REH is well established in economics literature because empirical evidence from previous studies is clearly mixed. This study used survey data on gross revenue and capital expenditures to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Nevertheless, it is interesting to note that optimistic bias in capital expenditure forecasts is rather typical in Malaysian business since previous studies by Habibullah (2003), Wong et al (2011), Puah et al (2013), and Chong et al (2012) have consistently revealed that business firms in other economic sectors also confront upward bias in capital expenditure forecasts. Wong et al (2011) regarded optimistic bias as a business goal to make the business outlook more attractive to potential investors, as optimistic capital expenditures reflect stronger business cultivation for the near future.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, it is interesting to note that optimistic bias in capital expenditure forecasts is rather typical in Malaysian business since previous studies by Habibullah (2003), Wong et al (2011), Puah et al (2013), and Chong et al (2012) have consistently revealed that business firms in other economic sectors also confront upward bias in capital expenditure forecasts. Wong et al (2011) regarded optimistic bias as a business goal to make the business outlook more attractive to potential investors, as optimistic capital expenditures reflect stronger business cultivation for the near future.…”
Section: Resultsmentioning
confidence: 90%
“…Those studies were carried out in two decades ago when the Malaysian economy was commodities-dominated and yet to enter into a rigorous transformation. Some recent studies by Puah, Chong, and Jais (2011), Wong, Puah, and Abu Mansor (2011), Chong, Puah, and Md Isa (2012), and Puah, Wong, and Liew (2013) have heightened the notion of forecast rationality in Malaysia's real and financial sectors. Nevertheless, the construction sector has had un-assessed business operational forecasts since the first and only work of Habibullah (1994a).…”
Section: Introductionmentioning
confidence: 99%
“…Testing for rational expectations has primarily relied upon comparing survey data on expectations to actual realizations. A recent example is from Puah et al (2013) who examined the rational expectations hypothesis in Malaysian manufacturing industries. However, according to prior studies (Lovell 1986;Svendsen 1993), evidence for rational expectations collected from such "direct" tests is weak.…”
Section: Rational Expectationsmentioning
confidence: 99%